Elderly healthcare reminder and wellness system / Nor Nazreen Khairi - Khairi, Nor Nazreen (2022)
This project describes the development of the medication web applications to help the elderly in cater their medications. Currently, dementia diseases frequently happened among older adults which are loss of cognitive performing thinking to such an extent which can interferes with a person’s daily life and activities. Managing medications is such a burden situation for the older adults as it could lead to medication non-adherence. Research about medication reminder and wellness web applications component has been made and found some of the criteria that need to be highlighted to help the older adults in decreasing the potential of medication non-adherence like practical research-based guidance, suggestions and recommendations on developing web application interfaces and other important forms of technology that convenient for the senior citizens use. This web application also will push a notification message based on the medication that has been recorded by the user. This project is focusing to fulfil what the client requirement which might have adjustment from time to time, the suitable methodology would be agile methodology instead of waterfall methodology since waterfall methodology is a well plan schedule and it will be less adjustment within the development. Agile Rapid Application Development or also known as RAD model is chosen for this research methodology. This project has argued that Elderly Healthcare Reminder and Wellness web application would be the best instrument to help the older adults in medicating their medications with the notification reminder features and also fulfil the adults need as it is coming with the spirituality element